Women Prisoners and the Drive for Desistance: capital and Responsibilization as a Barrier to Change - Hart, Emily Luise (Women & criminal justice, 2017)
There is a significant and growing volume of research into the way in which offenders desist from crime and their resettlement and reentry into society following a custodial sentence. As is too often the case in criminological research, women are underrepresented in these areas of investigation. This research aimed to investigate how women in the last 3 months of a prison sentence plan and prepare for their release. Using data generated from qualitative interviews with women prisoners and prison staff over a 13-month period in a closed women’s prison in England, this paper will argue that women prisoners have motivation and desire to desist from crime post-release, but their attempts to plan for release are hindered by a responsibilization discourse that runs throughout the institution and by a severe lack in all forms of capital (social, cultural, economic, and symbolic). This not only results in many women being released with little support in place to help them achieve their aims of a crime-free life in the future but also highlights the problems with a prison system based on male-centered knowledge.